(untitled) (Journal of the College of Basic Education, 2022)
The aim of the research is to identify “the difficulties of applying e-learning from the point of view of the teachers of the Arabic language departments in the colleges of basic education.” and its stability, and statistical packages (SPSS) were used to analyze the data, and the results revealed that the use of e-learning from the point of view of the faculty faces difficulties with a rate of (74.60%), and the order of these difficulties was as follows:In the first place were the difficulties related to students, in the second place were the difficulties related to evaluation, and in the third place came the difficulties related to university administration, and in the fourth place came the difficulties related to the curriculum, while the difficulties related to the teachers came in the fifth place.